(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Ayurveda is a traditional system of Indian medicine which aims to promote health and wellness by maintaining equilibrium of all three Dosas of body. Natural medicinal herbs are an important component of this science which aims to protect the body from various ailments and offer an user a variety of health benefits including physical as well as mental health. Haritaki has been placed in high esteem among all medicinal herbs due to its rich property to prevent and cure disease. It is always listed first in Ayurveda as it is called the king of medicines due to its large number of uses having extraordinary therapeutic benefits. Since ancient time, Haritaki has enjoyed a prime place among all medicinal plants. It is being found to be used in many of compound formulations due to its wide spectrum of pharmacological activities. Haritaki is one of three dried fruits that make up the Ayurvedic formula Triphala. It has been used among the large number of population to promote healing from variety of diseases ranging from use as Rasayan to the diseases related to indigestion and many more. Haritaki is being used as a best prescribed remedy for many of the common ailments in day today’s life by large number of physician. It is being used easily in all diseases, either for its health promoting benefit or for its disease alleviating property. Nowadays, using Haritaki as a single Dravya with various Anupaan is a great trend giving optimum results. Ekaldravya concept of using single substances has been mentioned in our ancient Ayurvedic literature. Use of Haritaki as a single drug therapy has been evidenced at various instances in Brihatrayee.